Dielectric and acoustic properties of modified barium titanate ceramics - Bormanis, Karlis Ya; Kalvane, Anna I.; Burkhanov, Anver I.; Eglite, L.; Dikov, R. V. (Taylor and Francis Inc., 2019)
A study of cobalt doping effect on the dielectric response and elastic properties of Ba0.95Pb0.05TiO3 solid solution within the range of 20–200 °C is reported. The results of a study of the dielectric permittivity, dielectric loss and elastic parameters in the samples of ceramic Ba0.95Pb0.05TiO3+xCo2O3 in the range of ferroelectric phase transition are presented. Modifying by admixture of Co is found to change the thermal anomalies of elastic and dielectric properties substantially, as well as to shift the ferroelectric phase transition temperature.
This work was supported in part by the Ministry of Education and Science of the Russian Federation.
Keywords: Research Subject Categories::NATURAL SCIENCES:Physics; barium titanate; doping; ferroelectrics; Perovskite